A Computational Investigation of the Insertion of Carbon Dioxide into Four‐ and Five‐Coordinate Iridium Hydrides. Issue 22 (13th May 2013) - Bernskoetter, Wesley H.; Hazari, Nilay
Abstract: Recently, it has been demonstrated that the insertion of CO2 into iridium hydrides is a crucial step in the catalytic conversion of CO2 and H2 into formic acid. We and others have elucidated the mechanism by which CO2 inserts into six‐coordinate iridium(III) trihydrides supported by pincer ligands; these complexes are very active catalysts for CO2 hydrogenation. However, it has also been demonstrated that five‐coordinate iridium(III) dihydrides can react with CO2 and catalyze both thermal and electrochemical CO2 hydrogenation. In this work, we study the mechanism of CO2 insertion into pincer‐supported five‐coordinate iridium(III) dihydrides and four‐coordinate iridium(I) hydrides using density functional theory. The mechanisms differ slightly between the two cases. Insertion into the five‐coordinate species is a multistep process involving initial CO2 precoordination, whereas insertion into the four‐coordinate species proceeds via a single step with no prior CO2 coordination. Both of these mechanisms are different from the pathway that was recently proposed for CO2 insertion into six‐coordinate iridium(III) trihydrides. In addition, a complete pathway for catalytic CO2 hydrogenation using a five‐coordinate iridium(III) dihydride has been calculated. Abstract : The insertion of CO2 into iridium hydrides has been proposed as a crucial step in the iridium‐catalyzed hydrogenation of CO2 . We used DFT to explore the mechanism of CO2 insertion into five‐coordinate iridium(III) dihydrides and four‐coordinate iridium(I) monohydrides with pincer ligands, and also calculated the catalytic cycle for thermal CO2 hydrogenation starting from an iridium(III) dihydride.